Microwave-Assisted Electroanalysis: A Review - Cutress, I; Marken, F; Compton, R (2009)
Microwave-assisted electrochemistry is critically discussed with a focus on the fundamental aspects of the processes involved and its applications in electroanalysis. The concept of direct and nondirect heated electrodes is discussed, and simulation work is evaluated. Microwave-assisted electrochemistry predominantly results in higher current responses (up to 2 magnitudes higher) due to increased temperature and mass transport to the active electrodes. Temperature gradients at microwave-affected electrodes may exceed 105 K/cm, with temperature hotspots found in the thin diffusion layers set up at ultramicroelectrodes. Research into microwave-assisted electroanalysis can lead to enhanced capillary electrophoresis detection, improved stripping voltammetry and development of new high temperature methods. © 2009 Wiley-VCH Verlag GmbH and Co. KGaA.